2016
DOI: 10.2319/010416-008.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rapid maxillary expansion on voice function

Abstract: Objective: To evaluate the effects of rapid maxillary expansion (RME) on vocal function in patients with bilateral maxillary crossbite. Materials and Methods: We designed our research as a prospective, controlled, clinical study. The treatment group and the control group each had 20 subjects for a total of 40 subjects. Acoustic voice samples were recorded from all patients at T 1 and T 2 by the Multi-Dimensional Voice Program (MDVP Model 5105) for acoustic analysis in Computerized Speech Lab (CSL). Results: No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…33 Although there are five formants for each vowel, two formants, namely F1 and F2, are most commonly used as indicators of vocal quality. 34 Yurttadur et al 20 detected a decrease in the F1 and F2 frequencies after removal of the RME appliance. Sari et al 21 suggested that vowels were affected by the size of the anterior oral cavity in patients who underwent surgically assisted RME.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…33 Although there are five formants for each vowel, two formants, namely F1 and F2, are most commonly used as indicators of vocal quality. 34 Yurttadur et al 20 detected a decrease in the F1 and F2 frequencies after removal of the RME appliance. Sari et al 21 suggested that vowels were affected by the size of the anterior oral cavity in patients who underwent surgically assisted RME.…”
Section: Discussionmentioning
confidence: 98%
“…13 In the literature, there is a paucity of information about the effect of RME on sound functions. 20 In this study, changes in voice quality and CT images before and after expansion were assessed in pediatric patients who underwent RME to investigate whether RME influenced voice quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the excluded studies [11], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63] divided the samples into treated and untreated control groups according to their chronological age and not according to their skeletal age. Seventeen studies [11], [21], [22], [26], [27], [36], [37], [38], [45], [46], [47], [51], [52], [54], [60], [63], [64], [65] had an untreated control group with normal occlusion or with other types of malocclusions other than posterior crossbites.…”
Section: Resultsmentioning
confidence: 99%
“…RME has many effects on the nasomaxillary complex other than transverse maxillary expansion and correction of crossbites. Effects of RME were studied on skeletal transverse, vertical and anteroposterior position of the nasomaxillary structures [84], [85], maxillary and mandibular transverse arch dimensions [86], [87], upper airway dimensions [88], [89], bite force, changes in the masticatory cycle and occlusal force distribution [90], swallowing [25] and condylar response [91], [92], [93], changes in head posture and scapular position, natural head position [94], enamel demineralization and white spot lesion formation [23], [57], hearing loss [95], [96], nocturnal enuresis [21], [97], [98], eruption of 3 rd molars [55], Class ll div1 [99], speech and voice function [58], [100], [101], obstructive sleep apnea(102), tongue posture [103] and Holdaway soft tissue analysis [104]. Effects of RME have also been studied on basal bone changes even in the absence of crossbites [105].…”
Section: Discussionmentioning
confidence: 99%